Experimental warming influences species abundances in a Drosophila host community through direct effects on species performance rather than altered competition and parasitism - Thierry, Mélanie; Pardikes, Nicholas A; Lue, Chia-Hua; Lewis, Owen T; Hrček, Jan (PloS one, 2021)
Global warming is expected to have direct effects on species through their sensitivity to temperature, and also via their biotic interactions, with cascading indirect effects on species, communities, and entire ecosystems. To predict the community-level consequences of global climate change we need to understand the relative roles of both the direct and indirect effects of warming. We used a laboratory experiment to investigate how warming affects a tropical community of three species of Drosophila hosts interacting with two species of parasitoids over a single generation. Our experimental design allowed us to distinguish between the direct effects of temperature on host species performance, and indirect effects through altered biotic interactions (competition among hosts and parasitism by parasitoid wasps). Although experimental warming significantly decreased parasitism for all host-parasitoid pairs, the effects of parasitism and competition on host abundances and host frequencies did not vary across temperatures. Instead, effects on host relative abundances were species-specific, with one host species dominating the community at warmer temperatures, irrespective of parasitism and competition treatments. Our results show that temperature shaped a Drosophila host community directly through differences in species' thermal performance, and not via its influences on biotic interactions.
Keywords: globální oteplování; interakce hostitele a parazita; Global Warming; Symbiosis; Drosophila; druhová specificita; zvířata; Climate Change; ekosystém; Temperature; symbióza; Ecosystem; klimatické změny; Host-Parasite Interactions; teplota; Species Specificity; Animals